ANALYSIS OF DA'WAH AND THE REPRESENTATION OF WOMEN'S SPIRITUALITY IN @Aniqqalfaqiroh's DA'WAH CONTENT - Safariyarti Saragih; Pahri Siregar; Mohd. Rafiq (Journal Analytica Islamica, 2026)
This research is motivated by the increase in digital da'wah which highlights women's spirituality emotionally and reflectively. The @aniqqalfaqiroh account has become the focus because it consistently discusses motherhood, marriage wounds, and women's inner recovery. This research formulates three main questions: how is the rhetoric of da'wah used, how is the representation of women's spirituality constructed, and what forms of da'wah are displayed in digital content. This research aims to analyze the da'wah rhetoric used in conveying messages about women's spirituality, examine the representation of women's spirituality in content, and identify forms of da'wah that are raised on the themes of motherhood and marriage wounds. Theoretically, this research uses Aristotle's rhetorical theory (ethos, pathos, logos), Stuart Hall's theory of representation, and the concept of women's spirituality in Islam as a basis for analysis. The research methodology used is a descriptive qualitative approach with narrative analysis methods. Data was obtained through in-depth observation of video content and Instagram uploads, content analysis, and interviews with relevant informants. The analysis technique is carried out by categorizing rhetorical elements, forms of preaching, and the construction of spirituality representations that appear in digital narratives. The research results show that @aniqqalfaqiroh's preaching rhetoric combines ethos, for example, seen in the credibility of sharing spiritual experiences and household reflections, fostering trust in the audience, pathos, for example from gentle language, empathy, touching feelings to form a space for women to recover, and logos, for example, seen in the invitation to understand life's trials as a destiny to get closer to Allah and spiritual strengthening for women. Women's spirituality is represented as an active subject interpreting life's trials through the role of mother, parenting knowledge, and inner healing. The forms of da'wah on the @aniqqalfaqiroh account can be seen through the application of da'wah bil hal, bil verbal, and bil qalam. For example, bil hal da'wah can be seen from Muslim women through Sharia clothing styles that reflect the values of faith, verbal bil for example through advice in content videos and Muslimah seminar classes, and bil Qalam for example through the books Spiritual Motherhood and Embracing Disappointment as a spiritual reflection